The Effectiveness Of Village Financial Management On The Welfare Of The People Of Lubuk Sepang Village, Pendopo District, Empat Lawang Regency - Khoir, Miftahul; Murlita (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Finding out the impact of village budget management on community welfare is the main objective of this research. It is important to determine whether the village finances in Lubuk Sepang Village, Pendopo District, Empat Lawang Regency are being used for the main requirements and priorities of the community's welfare. From December 2023 to February 2024, the research will be carried out. This study will make use of the quantitative research approach. Words, phrases, and pictures make up the qualitative data type. To conduct this kind of research, researchers compile passages of text from many sources, including people, books, and documents. A specific symptom or institution is the focus of thorough, detailed, and in-depth qualitative research. An technique to research known as qualitative research focuses on studying symptoms or natural occurrences. Many refer to this kind of research as "naturalistic inquiry" because of the emphasis on a more basic and empirical approach. Although it is required by law, the implementation of Village Fund Allocation management has been ineffective. As a way to facilitate land transportation for the community, the Lubuk Sepang Village, Pendopo District, Four Lawang Regency government prioritizes the development and maintenance of roads. This is in accordance with the community's interests and requirements. Also, from hamlet discussions to development planning talks, community involvement seems to be acceptable, if not perfect.